Exchange Rate Pass-Through, Domestic Competition, and Inflation: Evidence from the 2005/08 Revaluation of the Renminbi - Raphael A. Auer (Swiss National Bank, Study Center Gerzensee, 2014)
Import competition from China is pervasive in the sense that for many good categories, the competitive environment that US firms face in these markets is strongly driven by the prices of Chinese imports, and so is their pricing decision. This paper quantifies the effect of the government-controlled appreciation of the Chinese renminbi vis-à-vis the USD from 2005 to 2008 on the prices charged by US domestic producers. In a panel spanning the period from 1994 to 2010 and including up to 519 manufacturing sectors, import price changes of Chinese goods pass into US producer prices at an average rate of 0.7, while import price changes that can be traced back to exchange rate movements of other trade partners only have mild effects on US prices. Further analysis points to the importance of trade integration, variable markups, and demand complementarities on the one side, and to the importance of imported intermediate goods on the other side as drivers of these patterns. Simulations incorporating these microeconomic findings reveal that a substantial revaluation of the renminbi would result in a pronounced increase of aggregate US producer price inflation.
Keywords: F11; F12; F14; F15; F16; F40; E31; E37; L16; 330; Price Complementarities; Exchange Rate Pass-Through; China; Inflation; Monetary Policy; Exchange Rate Pass-Through; Außenhandelspreis; Wettbewerb; Mark-up Pricing; Inflation; Schätzung; USA; Renminbi; Aufwertung; China